Provisional heritability estimates of four distraction index traits in a breeding population of German Shepherd dogs. Issue 6 (2nd November 2018) - Tikekar, A; Soo, M; Lopez-Villalobos, N; Worth, AJ
Abstract : AIM: To obtain provisional estimates of the heritability ( h 2 ) of passive laxity of the coxofemoral joints of a breeding colony of German Shepherd dogs, measured using the PennHIP distraction index (DI). METHODS: Records were obtained of the PennHIP DI of right and left hips of 195 German Shepherd dogs (377 DI records) from the dog breeding colony of the New Zealand Police Dog Breeding Centre between 2003 and 2016, as well as pedigree records of 884 animals over four generations. Estimates of h 2 and variance components for the log transformed DI data were obtained using restricted maximum likelihood procedures with a single trait sire model. Four DI traits for each dog were analysed: left hip, right hip, mean and worse-hip DI. The model included the fixed effects of sex and year of birth, with the age at scoring as a covariable, the random sire effect and residual error for each observation. RESULTS: The h 2 of the DI of the left hip (0.81, SE 0.40) was higher than the h 2 of the DI of the right hip (0.35, SE 0.36). The h 2 for the worse-hip DI (0.15, SE 0.28) in each dog was lower than the h 2 of the individual hip DI, or the h 2 for the mean of the two hips (0.53, SE 0.36) in each dog. The low number of generations prevented a meaningful analysis of the genetic trend. CONCLUSIONS AND CLINICAL RELEVANCE: The h 2 estimates for the left, right and mean DI traits were moderate to high, whereas the h 2 estimates for the worse-hip DI (as used by the PennHIP programme for ranking of dogs) was low, but all estimates had large SE due to the small sample size. This provisional estimate of the h 2 of four distraction index traits suggests that the mean DI could be useful as a selection tool against canine hip dysplasia in German Shepherd dogs, whereas the worse-hip DI may be less effective. Heritability estimates from a population with a greater number of DI measures is needed to validate this finding given the large SE in our study.